A comparison of double single suture-button fixation, suture-button fixation, and screw fixation for ankle syndesmosis injury: A retrospective cohort study. Issue 13 (2nd April 2021) - Kurtoglu, Alper; Kochai, Alauddin; Inanmaz, Mustafa Erkan; Sukur, Erhan; Keskin, Dogan; Türker, Mehmet; Uysal, Mustafa; Sen, Zafer; Daldal, Ismail
Abstract : Abstract: Different methods have been used throughout the years for syndesmotic injury but there is no consensus on the ideal treatment. Some methods are expensive and some have more complications. The aim of this study is to compare single suture endobutton with double suture endobutton and screw fixation for syndesmotic injury. Sixty nine patients with syndesmotic injury with fibular fractures whom were treated with a single interosseous suture endobutton system (ZipTight TM, Zimmer Biomet), a double interosseous suture endobutton system (ZipTight TM, Zimmer Biomet) and 1 syndesmotic screw (TST, Istanbul, Turkey) were included in this study. Functional and radiological results from patient records between 2015 and 2018 were retrospectively evaluated. Twenty patients were treated with the double interosseous suture endobutton, 23 were treated with the single interosseous suture endobutton, and 26 were treated with traditional AO screw fixation. Three patients from the screw fixation group (11.5%) required revision surgery ( P < .05). All the radiologic and clinical outcomes were statistical similar in all 3 groups. Our findings showed that the interosseous suture endobutton system is at least as safe as the screw fixation technique for treatment of syndesmosis joint injuries and can be used as an alternative to the screw method. The interosseous suture endobutton system eliminates the need for a second surgery to remove the hardware, which minimizes the probability of re-diastasis. Since our results showed no statistical difference between single and double interosseous suture endobutton systems, the less costly single endobutton system may be the better alternative.